Conventional Adenoidectomy versus Endoscope-Assisted Adenoidectomy: Comparative Study - Raj, Amitha; Saldanha, Marina; Kalam, Ahsain S.; Aroor, Rajeshwari; Kamath, Shrinath D. (Journal of Health and Allied Sciences NU, 2024)
Objectives Adenoidectomy is a common surgical procedure in otorhinolaryngological practice.Conventionally, adenoidectomy is performed with a curette. The present study aims to compare the conventional method with the newer endoscope-assisted adenoidectomy method.Materials and Methods This prospective study was done in 36 patients requiring adenoidectomy at a tertiary care center from January 2020 to June 2021. The participants were allocated into two groups: group A (18) who underwent conventional adenoidectomy by curettage method and group B (18) who underwent endoscope-assisted microdebrider adenoidectomy. Data on indications for adenoidectomy, average surgical intraoperative time, and intraoperative blood loss were collected and compared between the groups. Postadenoidectomy symptom-based feedback was taken after 1 year. The intraoperative parameters were analyzed using mean ± standard deviation and independent t-test.Results The average operative timing in the conventional adenoidectomy group was 13.89 ± 4.837 minutes as compared with 19.44 ± 4.706 minutes in the endoscope-assisted adenoidectomy group (p = 0.001). The average amount of blood loss in the conventional group was 21.528 ± 2.51 mL whereas in the endoscope assisted group it was 24.889 ± 4.45 mL (p = 0.009). None of the patients had any symptoms suggestive of recurrence on 1-year follow-up.Conclusion Conventional adenoidectomy and endoscope-assisted adenoidectomy are safe and effective methods for adenoidectomy. Endoscopic adenoidectomy has the additional advantage of surgical removal under visualization. Depending on the clinical setup and with adequate training both procedures are effective.
Keywords: adenoidectomy; conventional curettage adenoidectomy; endoscopic; microdebrider